2020
DOI: 10.3389/fmicb.2019.03101
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Investigation Uncovers Potential Targets and Target Sites of Pneumococcal Serine-Threonine Kinase StkP and Phosphatase PhpP

Abstract: Pneumococcal StkP and PhpP Targets first time we were able to provide a list of previously unknown putative targets of PhpP. Under these new putative targets of PhpP are, among others, five proteins with direct involvement in cell division (DivIVA, GpsB) and peptidoglycan biosynthesis (MltG, MreC, MacP).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 98 publications
2
42
0
Order By: Relevance
“…(D) Total number of phosphosites and phosphoproteins identified from the three bacterial strains. (E) Comparison of these data to relevant related studies (Misra et al, 20 , 21 Prust et al, 12 Henry et al, 22 and Hirschfeld et al 23 ). (F) Histograms illustrating the distribution of the number of phosphosites per protein.…”
Section: Resultsmentioning
confidence: 95%
“…(D) Total number of phosphosites and phosphoproteins identified from the three bacterial strains. (E) Comparison of these data to relevant related studies (Misra et al, 20 , 21 Prust et al, 12 Henry et al, 22 and Hirschfeld et al 23 ). (F) Histograms illustrating the distribution of the number of phosphosites per protein.…”
Section: Resultsmentioning
confidence: 95%
“…Many substrates of PASTA-eSTKs have been identified in the different Gram-positive bacteria. Among these kinase substrates are proteins from various cellular pathways, but some functional classes are overrepresented: (i) Proteins acting in carbon and cell wall metabolism such as the HPr and YvcK proteins of B. subtilis and L. monocytogenes (28, 4244), (ii) regulatory proteins such as the WalR and GraR response regulators of B. subtilis and Staphylococcus aureus , respectively (45, 46), and (iii) proteins acting in cell division, among which GpsB is one of the proteins consistently found as a PASTA-eSTK substrate in B. subtilis, L. monocytogenes and Streptococcus pneumoniae (28, 47, 48). This diversity of substrates and their own – often pleiotropic - functions have impeded the identification of primary and the discrimination of less important kinase substrates.…”
Section: Discussionmentioning
confidence: 99%
“…In S.pneumoniae , a mass-spectrometry based label-free quantitative (LFQ) approach was used to characterize and determine the impact of StkP on the protein expression profiles. Notable changes in the proteome of the kinase mutant ΔstkP in comparison to the WT strain have been observed especially in the cluster of amino acid metabolism, energy metabolism, regulatory fuction and transcription(Hirschfeld et al 2019 ). In the present study, comparative proteomics approaches revealed that SsSTK can regulate the expression of proteins involved in bacterial central metabolism, stress response and virulence.…”
Section: Discussionmentioning
confidence: 99%